Urgency of Cyber Notary Application In The Pandemic of Covid-19 For The Need of Authentic Deed - Isa Anshari Arif; Nynda Fatmawati Octarina (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
This article aims to find out the urgency about the application of Cyber Notary in the recent times that are experiencing a covid-19 pandemic, this research uses a normative method with deductive logic that explains a general thing then draws it to a specific conclusion. That Cyber Notary should have been implemented in Indonesia where it has previously been provided with facilities in Article 6 of the ITE Law and Article 77 paragraphs (1) and (4) of the Company Law, but because the UUJN-P has not yet regulated and as a lex specialis notary position, the Cyber Notary not applicable yet. However, this must be considered again, considering that during the covid-19 era, which was expected to reduce activities outside the home, to reduce the risk of covid-19 virus and not reduce legal services to the community in the form of making authentic deeds. For the implementation of Cyber Notary requires the requirements in the form of changes to several articles in the legislation namely: (1) Article 1868 of the Civil Code, (2) Articles in UUJN-P, (3) Article 5 paragraph (4) in UU ITE, and ( 4) The Stamp Duty Act which has always identified authentic deeds is always in the form of a written deed. And to reduce the security risks of Cyber Notary, external factors that must be considered are: (a) notary ethics, (b) ongoing notary education, (c) electronic data security techniques, and (d) certification authorization.